Factors influencing health literacy 3E2S concept among the elderly in Pathum Thani Province - Yothasupap, Aussadawut; Ounhalekjit , Pakpoom (Journal of Medical and Public Health Region 4, 2025)
This research study is a cross – sectional descriptive study. To study the level of health literacy according to the principles of 3E2S. and factors affecting health literacy according to the principles of 3E2S of the elderly in Pathum Thani Province. The study sample consisted of 317 people aged 60 years and over using multi-stage sampling. Collected using a questionnaire with an Index-Objective Congruence (IOC) was 0.892 Cronbach's Alpha Coefficient for the entire version was 0.876. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and deviation. Standard inferential statistics include Eta coefficient statistics, Pearson's Correlation coefficient, and multiple regression. The resulted of the study found that the majority of the sample had an overall level of health literacy at a fair level, accounting for 42.0 percent. And the results of the analysis of factors affecting health literacy found that the ability to use technology Interpersonal factors Receiving information and factors at the overall social level affecting health literacy according to the 3A.2S principles of the elderly in Pathum Thani Province, which can predict health literacy according to the principles of 3A.2S. of the sample at 63.2 percent (R2=0.632). Therefore, we should have to create interactions between people in the family. Public health officials and the elderly are focusing on developing skills in accessing useful information. By selecting online health media and practicing data analysis, health personnel provide advice to ensure that the elderly maintain good health and a high quality of life.